Infectious Bursal Disease Virus in Algeria: Persistent Circulation of Very Virulent Strains in Spite of Control Efforts - Chafik Redha Messaï; Nadia Safia Chenouf; Oussama Khalouta; Abdelhafid Chorfa; Omar Salhi; Claudia Maria Tucciarone; Francesca Poletto; Giovanni Franzo; Chahrazed Aberkane; Mattia Cecchinato; Matteo Legnardi (Animals)
Infectious bursal disease (IBD) is among the most impactful immunosuppressive diseases of poultry. Its agent, infectious bursal disease virus (IBDV), is prone to both mutation and reassortment, resulting in a remarkable variability. Traditionally, IBDV characterization relies on antigenicity and pathogenicity assessment, but multiple phylogenetic classifications have been recently proposed, whose implementation in molecular surveys helps generating informative and standardized epidemiological data. In the present study, the Algerian IBDV scenario was assessed based on the novel classification guidelines by sequencing portions of both genome segments. Seventy pools of bursal samples were collected in 2022–2023 in 11 districts of Northern Algeria, mostly from broiler flocks. Out of 55 (78.6%) positive flocks, 40 (57.1%) were infected by field strains, which were characterized as very virulent strains (genotype A3B2) and phylogenetically related to previously reported Algerian strains. Significant differences in the percentage of field infections were observed between vaccinated (25/52, 46.2%) and unvaccinated (14/17, 82.3%) groups, and also between birds immunized with live intermediate (13/20, 65.0%) and intermediate plus (10/28, 35.7%) vaccines. Nonetheless, the number of field strain detections suggests a high infectious pressure and the inadequacy of current vaccination efforts, demanding a reevaluation of control measures coupled with attentive monitoring activities.